Duchenne muscular dystrophy: RANK/RANKL/OPG (receptor activator of nuclear factor-kB/RANK ligand/osteoprotegerin) system and glucocorticoids - Salvador Atilano-Miguel; Lourdes Barbosa-Cortés; Rocío Ortiz-Muñiz (Permanyer, 2022)
Duchenne muscular dystrophy (DMD) is an X-linked inherited disorder. Patients present with decreased bone mineral density (BMD) due to glucocorticoid therapy and progressive muscle weakness. Bone remodeling allows bone volume and structure to be maintained and controlled by local and systemic factors. These include the receptor activator of the nuclear factor-kB (RANK)/RANK ligand (RANKL)/osteoprotegerin (OPG) system, a determining pathway in the balance between bone formation and resorption. Disruptions in this complex, caused by factors such as glucocorticoids, can affect bone metabolism. The extensive action of the RANK/RANKL/ OPG pathway suggests an influence on dystrophic muscle pathophysiology. This review aimed to highlight some aspects of the RANK/RANKL/OPG system, the effect of glucocorticoids on this pathway, and the pathophysiology of the patient with DMD.